Penerapan Model Pembelajaran Matematika Melalui Pemecahan Masalah untuk Meningkatkan Penalaran Matematis Siswa Kelas X-A SMA Al-Muslimun - Maimunah, Maimunah; Purwanto, Purwanto; Sa’dijah, Cholis; Sisworo, Sisworo (UIN Sunan Ampel Surabaya, 2016)
The purpose of this study to improve students mathematical reasoning with the application of teaching mathematics through problem solving. This models consist of four fase, that is: giving problems, investigation, presentation results, and evaluation results. Method of research is quasi experimental is implemented in class X-A SMA Al Muslimun Pelalawan Riau. Subject of this study were 19 students who divided into groups of 4-5 students with the capability of high, medium, and low. The instrument used was a test and observation. In the pretest result there were 10 students with sufficient reasoning and good criteria. While on the posttest there were 19 students with the criterion of mathematical reasoning is good. No students obtains criterion of mathematical reasoning is very good in two test.